A knowledge transfer framework for virtual projects. (30th November 2004) - Bosch-Sijtsema, Petra M.
Organisations increasingly work in virtual settings. However, few studies discuss knowledge transfer in virtual settings. In this paper, we discuss two questions: (a) To what parties is the knowledge transferred in virtual projects; we present a framework of knowledge transfer to different stakeholder parties. (b) Second, what kind of knowledge (content, organisational and social) is transferred to the stakeholders of a virtual project? Three case studies have been examined in order to answer these questions. It was found that the more virtual cases (complete dispersion of the workforce) transferred less tacit knowledge. Furthermore, the transfer of organisational and social knowledge became important in more virtual settings compared to a case study with physical proximity.